OC-079 FGF19 expression is highly responsive to bile acids compared to other bile acid regulatory genes within the human ileum. (28th May 2012) - Nolan, J D; Zhang, J H; Johnston, I; Kennie, S; Dew, T; Dixon, P; Williamson, C; Walters, J R
Abstract : Introduction: The expression of the enteric hormone FGF15 is largely restricted to the ileum in the mouse. FGF15 has also been shown to be the most BA responsive gene in mouse ileum. FGF19 is the human orthologue of FGF15 and is thought to have roles in the regulation of bile acid pool sizes and BA homeostasis. We set out to investigate the distribution of FGF19 expression in the human GI tract and FGF19 gene responses to BA in human ileum. Methods: Biopsies of normal ileal mucosa were obtained from 29 patients undergoing colonoscopy. Basal ileal FGF19 expression was compared to colonic (n=9) and duodenal FGF19 expression (n=3). Ileal biopsies (explants) from 20 patients were incubated for 6h in short term tissue culture in parallel with BA (chenodeoxycholic acid [CDCA] or glyco-chenodeoxycholic acid [GCDCA]) or without (control explants). 3 Duodenal and colonic explants from were also studied. Real-time qRT-PCR was used to measure expression of transcripts for FGF19, and several other ileal BA regulatory genes (ASBT, IBABP, SHP, FXR, OSTα and OSTβ). FGF19 protein levels in culture fluid were also measured by specific ELISA. Results: Transcripts for FGF19 were detected in human ileum, but not colon or duodenum. FGF19 expression was greatly induced in all ileal explants incubated with BA: geometric mean induction of 316-fold by 50 μM CDCA (n=17, p=0.0003), and 231-fold by 50 μM GCDCA (n=11, p=0.001). Measured by ELISA, the amount of FGF19 protein released into the culture media was significantly higher from the explants incubated with 50 μM of BA (CDCA 51 pg/explant, range 8–169, n=11 and GCDCA 38 pg/explant, range 3–113, n=10) compared to the matched control explants (8pg/explant, range 0–46 [p=0.0008] and 6 pg/explant, range 0–13 [p=0.0022] respectively). The EC50 for CDCA was 20 μM and 24 μM for GCDCA. Responses to both BA were similar at 50 μM and 100 μM. 6 h incubation of duodenal and colonic explants with 100 μM CDCA or GCDCA showed that FGF19 expression levels were <0.35 times the FGF19 expression seen in the control ileal explants at 6 h. In ileal explants, responses of other genes to CDCA and GCDCA at 50 μM (n=3–4) showed median increases for IBABP, OSTα, OSTβ and SHP between 2.4 and 4.0-fold, whereas ASBT and FXR showed little change. Conclusion: FGF19 is expressed in human ileum but not the colon or duodenum. Ileal FGF19 expression is highly responsive to CDCA and GCDCA, compared to other BA regulatory genes. No significant induction of FGF19 expression is observed in duodenum or colon with BA. Ileal BA induced FGF19 responses could be studied in clinical conditions of dysregulated BA homeostasis. Competing interests: None declared.